2020
DOI: 10.1200/jco.2020.38.6_suppl.76
|View full text |Cite
|
Sign up to set email alerts
|

Safety and outcome of stereotactic body radiation therapy (SBRT) with rectal hydrogel spacer for prostate cancer.

Abstract: 76 Background: Ultra-hypofractionated radiotherapy delivered using stereotactic body radiotherapy (SBRT) is a cost-effective treatment for localized prostate cancer. Optimal dosing remains unclear, as commonly used 30-40Gy/5fx regimens appear to overestimate hypofractionation’s control benefits. Here, we report the largest experience of 45Gy/5Fx of SBRT for prostate cancer patients treated with hydrogel peri-rectal spacer (‘hydrogel’). Methods: An IRB-approved retrospective protocol was used to conduct a regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…16,17 Second, while infrequent but severe rectal toxicity has been observed with high dose SAbR in early studies without spacer gel, as reported by our group, 10,15 the patient's rectal dosimetry fell well within institutional constraints developed based on those experiences 15 and largely met constraints of lower SAbR dose regimens (Table 1). Notably, in our own institution's prospective 13 and retrospective 11 experiences because initiation of rectal hydrogel spacer placement with high dose SAbR across all risk groups (n = 250), no other single case of grade >2 rectal toxicity has been noted. 11 Third, rectal wall infiltration in retrospect was of substantial depth and resulted in an area of delamination of deep rectal wall muscle layers, best approximated on sagittal sequences.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…16,17 Second, while infrequent but severe rectal toxicity has been observed with high dose SAbR in early studies without spacer gel, as reported by our group, 10,15 the patient's rectal dosimetry fell well within institutional constraints developed based on those experiences 15 and largely met constraints of lower SAbR dose regimens (Table 1). Notably, in our own institution's prospective 13 and retrospective 11 experiences because initiation of rectal hydrogel spacer placement with high dose SAbR across all risk groups (n = 250), no other single case of grade >2 rectal toxicity has been noted. 11 Third, rectal wall infiltration in retrospect was of substantial depth and resulted in an area of delamination of deep rectal wall muscle layers, best approximated on sagittal sequences.…”
Section: Discussionmentioning
confidence: 88%
“…Notably, in our own institution's prospective 13 and retrospective 11 experiences because initiation of rectal hydrogel spacer placement with high dose SAbR across all risk groups (n = 250), no other single case of grade >2 rectal toxicity has been noted. 11 Third, rectal wall infiltration in retrospect was of substantial depth and resulted in an area of delamination of deep rectal wall muscle layers, best approximated on sagittal sequences.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations